Caracterización agronómica de 12 cultivares de café robusta (Coffea canephora) en la época lluviosa, en el Cantón Mocache, Provincia de Los Ríos. - Olvera Vélez, Helen Antonella (2019)
At present, Ecuadorian coffee is in a critical situation because the low productivity and poor quality of the grain, due to the cultivation in marginal areas, use of unknown genetic material and very high production costs. The objective of this research work is to establish the agronomic characteristics of 12 robust coffee cultivars (Coffea canephora). The field phase was completed during the rainy season, February / 2019- June / 2019 at the Experimental farm “La María” in the Mocache canton. It was established in a plantation of approximately 2 years. The clones of robust coffee are separated by plots of 135 m2 with 24 plants of which the useful area of the plot conformed by 8 plants is delimited to establish the agronomic characteristics according to the Completely Random Design: 1) GCNU-1; 2) JCL-6; 3) ACR-2; 4) HC-501 5) NP 2024; 6) JG-01; 7) JMR-8; 8) CGS-2; 9) CONILON; 10) BC -01; 11) ECUROBUSTA; 12) HP 3056-P10. The following variables were recorded: plant height, stem diameter, number of leaves, number of plagiotropic branches, number of internodes, branch length, plant vigor, number of shoots, leaf coloration, flowering and pest diseases that presented the clones. From the analysis and interpretation of the results it was concluded that the highest plant height with 107.81 cm and length of plagiotropic branch 54.06 cm is recorded by the ACR-2 clone; the clone with the highest number of plagiotropic branches was JMR-8 with 38.1 and the clone with the largest stem diameter 19.75 mm and vigor was ECUROBUSTA.The application of Lactical every 15 days and dolomite lime, positively influenced the increase in soil pH, and resulted in the increase of a significant gap ratified by the soil analysis that shows an increase in the soil, the treatments did not obtain a significant response to the application of organic foliar fertilizers, but it presented an increase in organic matter in all treatments. The results suggest an acute nutritional imbalance in the crop, corroborated by the soil analysis that shows a low availability of N, and its imbalance in relation to Mg / K and (Ca + Mg) / K. The cause is the prolonged exploitation of the soil omitting the necessary fertilization and amendments. Keywords: clones, vigor, pH, coffee.